Escalation as a way to resolve conflicts and contradictions - J. G. Evdokimova; S. M. Sycheva; T. B. Shramchenko; E. A. Khalimon (Вестник университета)
The domestic and foreign practice of project conflict management and resolution is analysed. The concepts of “conflict” and “contradiction” are differentiated. The modern point of view on the essence of the conflict is revealed, suggesting that the conflict does not always have negative consequences. In some cases, it is necessary to increase the effectiveness of the project implementation, so sometimes managers are required to stimulate its development (escalation of the conflict). The specific features of the escalation of the conflict and its relevance in a particular conflict situation are determined. The psychological features of the conflict escalation are analysed, which are manifested in the reluctance of domestic leaders to take the problem higher because of the fear of not being able to cope with the management of the conflict. Strategies for managing project conflicts are highlighted, and a conceptual model for managing them is proposed.